KORELASI TANDA-TANDA FISIS PADA IRIS TERHADAP KELUHAN DISMENORE PADA WANITA - , AGATHA MAHARDIKA ANUGRAYUNING JIWATAMI, Dr. Gede Bayu Suparta ([Yogyakarta] : Universitas Gadjah Mada, 2011)
A research to find out the correlation of the physical signs of reproduction organ area in iris (ovarium and uterus) to dysmenorrhea complaints on woman has been carried out. Monitoring is done by capturing left and right iris image from woman between 21 and 29 years old. The left and the right iris images are grouped in 4 level of pain based on dysmenorrhea complaints. They are no pain, less pain, pain and lots pain. To capture images, SLR camera uses zoom lens 70 -200 mm coupled with macros filter to shorten minimum focus distance between eye and lens. Artificial lighting is straightly pointed to iris area to capture detail information. Camera is steadied by tripod to reduce shake. Image is analyzed by software ImageJ to enhance its quality. Result of the research shows that the more woman dysmenorrhea complaints, the longer, wider and darker line on iris. The length line estimation on samples ovarium area which are donât feel pain is 0,15 mm â 0,74 mm, samples which are feel less pain is 0,19 mm â 1,09 mm, samples which are feel pain is 0,63 mm â 1,27 mm and samples which feel lots pain is 0,63 mm â 1,92 mm. The length line estimation on samples ovarium area which are donât feel pain is 0,30 mm â 0,69 mm, samples which are feel less pain is 0,38 mm â 1,33 mm, samples which are feel pain is 0,41 mm â 1,42 mm and samples which feel lots pain during menstruation is 0,38 mm â 1,71 mm.